2018
DOI: 10.3389/fpsyg.2018.01165
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Perceptions of Adverse Peer Experiences in First-Grade Students

Abstract: Aim: The aim of this study was to identify which adverse peer experiences better predict perceived negative peer relationships among elementary school first graders according to sex. The peer experiences examined were peer rejection, peer victimization, and mutual antipathy; the interpersonal perceptions studied were perceived peer victimization, dyadic meta-perception of peer disliking, and loneliness.Methods: The participants were 809 children (Mage = 6.4 years, SD = 0.32; ngirls = 412, 50.9%) enrolled in 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
(128 reference statements)
0
5
0
1
Order By: Relevance
“… Sidera et al (2020) explain that this misperception can be related to the type and quantity of bullying actions that someone experiences. These students may not be aware of being disliked if they are not overtly disliked and treated aversively by their peers ( García Bacete et al, 2018 ). Thus, some victimized students may habituate to direct verbal and physical aggression and would normalize such behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Sidera et al (2020) explain that this misperception can be related to the type and quantity of bullying actions that someone experiences. These students may not be aware of being disliked if they are not overtly disliked and treated aversively by their peers ( García Bacete et al, 2018 ). Thus, some victimized students may habituate to direct verbal and physical aggression and would normalize such behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, authors such as Kilpatrick et al (2019) found that bullying mediated the effect between a history of DLD and internalizing symptomatology (depression, anxiety, etc.). This situation might lead to a more obvious sociometric profile of rejection by class peers ( García Bacete et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A esta corta edad, parece que las chicas perciben más, o saben interpretar mejor, las pistas sociales que los chicos. Más concretamente, parece que las chicas son más sensibles a las muestras de rechazo de los compañeros-as (García Bacete, Sureda-García, et al, 2018). Esto haría que fallasen menos que los chicos en omisión de rechazadores.…”
Section: Discusión Conclusionesunclassified
“…Having a positive peer relationship with classmates is important during the elementary school years. Elementary school children who are not liked by their classmates or who have no or only a few friends are at risk of bullying [8,9] with associated emotional and behavioral needs [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Having a positive peer relationship with classmates is important during the elementary school years. Elementary school children who are not liked by their classmates or who have no or only a few friends are at risk of bullying [8,9] with associated emotional and behavioral needs [10][11][12][13].Teachers can support mental health among elementary school children [14]. Thus, children's access to supportive adults, particularly teachers, is important [15][16][17][18][19][20].…”
mentioning
confidence: 99%